PENATAAN ULANG ORGANISASI DENGAN MODERN QUALITY MANAGEMENT - Wahyu Purhantara (Universitas Negeri Yogyakarta, 2010)
Changing business environment always force any business organization, both in manufacture as well as in service, to make adjustments. These are related to the future and survival of the organization. For a developing organization, along with its live cycle, it must reorganized itself. There fore, there should be a reconsideration to the culture of the organization, its vision and mission, and its commitment to reinventing organization. Modern quality management (MQM) is one of the solutions offered to rearrange the organization. The MQM concept will transform all components of the organization, so that will be able to create any changes in order to develop, have competitive advantages and provide satisfaction to customers. Keyword: reinventing organization, change management, and modern quality management